Assessing the impact of petroleum sludge ash on the compressive strength of fly ash-palm oil clinker geopolymer mortar - Ismail, Amalina Hanani; Kusbiantoro, Andri; Tajunnisa, Yuyun (2023)
Oil industries are one of the most critical industries with substantial production and closely related to the public interest. Two major oil industries, namely petroleum and palm oil, represent primary sources of consumer groups in Malaysia. However, these sectors inevitably generate waste and require disposal systems. Massive amounts of petroleum sludge generated from the refinery process, possess toxic contaminants requiring careful disposal. Similarly, palm oil production generates a hefty amount of by-products from its extraction process. Encapsulating these wastes in a cementitious medium is considered a more feasible solution than converting them for landfilling. Therefore, this study aims to utilize two wastes from palm oil and petroleum industries as binder materials in a geopolymer framework. To achieve this, palm oil clinker and petroleum sludge as the by-products from those respective industries, were subjected to mechanical grinding and incineration processes to improve their reactivity. Palm oil clinker powder (POCP) was included in the geopolymer mixture to replace 2.00–10.00% of fly ash as the source material. After obtaining the optimum POCP replacement, 0.20–1.00% of petroleum sludge ash (PSA) to be included in the geopolymer mortar to assess its impact on geopolymerization. Compressive strength was evaluated on 7, 28, and 90 days to determine the optimum proportion of fly ash, palm oil clinker, and petroleum sludge ash in geopolymer, particularly the proportion that carries the least negative effect onto the compressive strength performance. Based on the results, the ratio of 91.30% fly ash, 7.60% POCP and 1.10% PSA provided the most significant strength improvement among its peers. The encapsulation task of petroleum sludge